Novel POSS (Polyhedral Oligomeric Silsesquioxane) and preparation method thereof as well as oral cavity restoration low-shrinkage composite resin as well as preparation method and application thereof
By introducing a new POSS with reactive double bonds and epoxy shrinkage groups into the oral resin, the tooth gap and secondary caries caused by polymerization and shrinkage are solved, and the design of low-shrinkage composite resin is realized, and the durability of the material is improved. and stability, extending service life.
Patent Information
- Application Number
- CN202411853926.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-01-14
AI Technical Summary
During the repair process, existing oral resin materials have polymerization and shrinkage, which leads to gaps between the tooth and the restoration resin, which in turn causes secondary caries and micro leakage, affecting the durability and service life of the restoration material.
Using a new polyhedral oligosilsesquioxane (POSS) with reactive double bonds and epoxy shrinking groups, it is prepared by hydrolysis-polycondensation reaction, combining other organic components and fillers, a low-shrinkage composite resin is designed to reduce the shrinkage of the resin. Sexual and hydrophilic, prolonging service life.
It effectively reduces the polymerization shrinkage rate of oral repair composite resin, improves mechanical properties and stability, extends service life, reduces the generation of microcracks and micro leakage, and enhances the hydrophobicity and mechanical properties of the resin.
Smart Images

Figure CN119306948A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedical oral materials, and specifically relates to a novel POSS with reactive and low shrinkage characteristics and a preparation method thereof, as well as an oral restoration low shrinkage composite resin based on the novel POSS and a preparation method thereof and application in the oral field. Background Art
[0002] The oral cavity is an important way for the human body to take in external food, and its health level is crucial to the human body. Long-term lack of proper oral care can cause a variety of oral problems such as oral ulcers, periodontal disease, dental caries, bad breath, etc. Among them, dental caries is the most common disease among oral problems. Bacteria, sugary foods and the body's anti-caries ability are the three important pathogenic factors of dental caries.
[0003] During the restoration process of dental caries with resin filling materials, the organic monomers in the resin are polymerized by photoinitiators to form polymers with a cross-linked network structure, so that the molecular components in the oral resin form a covalent and tight arrangement of atoms, causing the polymerized resin to shrink in volume. The gap between the tooth and the restorative resin is formed by the growth of oral bacteria to form a plaque biofilm, which then corrodes the tooth and the restorative material, leading to secondary caries and restoration failure. Oral resin materials have become widely used clinical dental restorative materials due to their excellent properties such as aesthetics, mechanics and biocompatibility. Methacrylate resin is an important component of them, and its performance is better than that of amalgam, ceramics and metal polymer materials. Low-shrinkage composite resins are an important way to reduce microleakage and secondary caries. Designing low-shrinkage monomers and applying them to low-shrinkage restorative resins is an important direction for improving oral restorative resins.
[0004] The organic monomer in the composite resin is the main factor affecting the polymerization shrinkage stress. The higher the polymerization shrinkage rate, the greater the shrinkage stress of the resin, and the greater the probability of causing secondary caries and microleakage. The use of expandable monomers and ring-opening monomers is an important method to reduce the polymerization shrinkage of resins.
[0005] In order to solve the above problems encountered in the application and treatment of oral resins, its components need to be modified. Polyhedral oligomeric silsesquioxane (POSS) is a hydrophobic organic-inorganic hybrid nanomaterial with the advantages of good biocompatibility, non-toxicity, good stability, and functional modification of various R groups at the vertex angles. It can enhance the performance of the matrix and maintain good biocompatibility at the micron or nanometer level. Its nano-rigid cage structure remains unchanged before and after the polymerization reaction, which can reduce the polymerization shrinkage of the composite resin and maintain stable mechanical properties. POSS is hydrophobic, and the oral restoration composite resin prepared based on it can effectively solve the problem of performance degradation of oral resins due to water absorption and hydrolysis during use, so as to extend the service life of oral restoration composite resins.
[0006] Therefore, there is an urgent need to develop a new type of POSS monomer for oral restoration composite resin to improve the durability of oral restoration composite resin filling or repair and extend the service life of oral restoration composite resin materials. Summary of the invention
[0007] In view of the deficiencies in the above-mentioned prior art, the present invention provides a new type of POSS having reactive double bonds and epoxy shrinkage groups and a preparation method thereof, as well as an oral restoration low-shrinkage composite resin based on the new type of POSS and a preparation method thereof and application in the oral field, so as to improve the durability of oral restoration composite resin filling or restoration and extend the service life of oral restoration composite resin materials.
[0008] The specific technical solutions are as follows: The first object of the present invention is to provide a method for preparing a novel POSS, comprising the following steps: mixing trimethoxy[2-(7-oxabicyclo[4.1.0]hept-3-yl)ethyl]silane, a double bond-containing silane and an organic solvent, obtaining a liquid material through a hydrolysis-polycondensation reaction, and obtaining a product after liquid separation, suction filtration, washing, rotary evaporation and drying, namely the novel POSS.
[0009] Furthermore, the usage ratio of the trimethoxy[2-(7-oxabicyclo[4.1.0]hept-3-yl)ethyl]silane, the double bond-containing silane and the organic solvent is 0.1-1 mol: 0.1-1 mol: 1-500 mL.
[0010] Furthermore, the pH value of the liquid material is 5-13.
[0011] Furthermore, the reaction temperature of the hydrolysis-polycondensation reaction is 40-80° C., and the reaction time is 18-36 h. Preferably, the reaction temperature is 50-60° C., and the reaction time is 20-30 h.
[0012] Furthermore, the reaction atmosphere is air atmosphere or inert protective atmosphere.
[0013] Furthermore, the double bond-containing silane includes methacryloxypropyltrimethoxysilane and the like.
[0014] Further, the organic solvent is selected from one or more of alcohols (including but not limited to methanol, ethanol, isopropanol, etc.), ketones (including but not limited to acetone, methyl isobutyl ketone, etc.), ethers (including but not limited to diethyl ether, tetrahydrofuran, etc.), esters (including but not limited to ethyl acetate, butyl acetate, etc.), halogenated hydrocarbons (including but not limited to dichloromethane, chloroform, etc.), aromatic hydrocarbons (benzene, toluene, xylene, etc.), dimethyl sulfoxide, tetrahydrofuran, acetonitrile, N,N-dimethylformamide, etc.; preferably ketones (including but not limited to acetone, methyl isobutyl ketone, etc.) and ethers (including but not limited to diethyl ether, tetrahydrofuran, etc.).
[0015] Furthermore, the reagents used in the hydrolysis-polycondensation reaction include commonly used bases, preferably water-soluble bases.
[0016] The second object of the present invention is to provide a novel POSS, which is prepared by the preparation method of the novel POSS as described above.
[0017] Further, the novel POSS has a structure shown in Formula 1:
[0018] Formula 1 The novel POSS is a cage-like structure, wherein the cage angle range is 5 <T<25。
[0019] The invention designs and synthesizes a reactive POSS low-shrinkage oral resin organic component with low shrinkage characteristics and capable of participating in polymerization, wherein the main molecular body is a cage-shaped POSS structure of Si-O-Si, and the reactive group at the top of the POSS molecular cage has both a double bond capable of participating in polymerization reaction and an epoxy group capable of ring-opening reaction, thereby reducing the shrinkage of the oral repair resin and forming a cross-linked network of the oral resin matrix together with other organic components. The oral repair low-shrinkage composite resin is designed based on the synthesized epoxy double-bond POSS, and the POSS component has hydrophobicity, thereby reducing the hydrophilicity of the oral repair resin and the performance degradation caused by hydrolysis during long-term use, and esterification of some components in the presence of water, thereby extending the service life of the oral repair resin and avoiding the reduction of the service life of the oral repair composite resin due to hydrolysis.
[0020] The third object of the present invention is to provide a method for preparing a low-shrinkage composite resin for oral restoration, comprising the following steps: preliminarily mixing raw material organic components, fillers, a photoinitiator system, and the novel POSS as described above, mixing them in a three-roll grinder, and then subjecting them to vacuum negative pressure treatment to obtain an uncured composite resin raw material, and obtaining a resin matrix after photocuring, i.e., the low-shrinkage composite resin for oral restoration.
[0021] Furthermore, the organic component accounts for 10-99% of the total weight of the raw materials, the filler accounts for 0-80% of the total weight of the raw materials, the photoinitiator system accounts for 1-5% of the total weight of the raw materials, preferably 1.5-3%; the new POSS accounts for 1-30% of the total weight of the raw materials, preferably 5-20%.
[0022] Further, the organic component is selected from one or more of butyl acrylate, methyl methacrylate, isobornyl acrylate, hydroxyethyl methacrylate, caprolactone acrylate, isodecyl acrylate, polyethylene glycol monoacrylate, 2-phenoxyethyl methacrylate, 1,6-ethylene glycol diacrylate, dipropylene glycol diacrylate, bisphenol A epoxy acrylate, propoxylated neopentyl glycol diacrylate, triethylene glycol dimethacrylate, trimethylolpropane triacrylate and pentaerythritol triacrylate.
[0023] Further, the organic component is selected from one or more of methyl methacrylate (MMA), ethylene glycol dimethacrylate, bisphenol A-dimethacrylate glycidyl ester (Bis-GMA), polyurethane acrylate methacrylate resin (UDMA), triethylene glycol dimethacrylate (TEGDMA), glycidyl methacrylate (GMA), and other commonly used organic components in the industry and the functional new POSS prepared by the present invention. The compatibility between the functional new POSS component and the above organic components is applicable.
[0024] Further, taking Bis-GMA and TEGDMA as an example, the proportion of Bis-GMA in the resin is 40-49%, and the proportion of TEGDMA in the resin is 40-49%, and preferably the weight ratio of Bis-GMA to TEGDMA is 1:1.
[0025] Furthermore, the filler is selected from one or more of silicon dioxide, glass powder (including various metal oxides, such as silicon dioxide, calcium oxide, sodium oxide, etc.), ceramic powder and other common fillers in the field of oral resins, and the filler is a mixture of micron-scale and nano-scale.
[0026] Furthermore, the photoinitiator system is selected from a photoinitiator, a combination of a photoinitiator and a thermal initiator, or a combination of a photoinitiator and a co-initiator.
[0027] Furthermore, the photoinitiator is selected from one or more of camphorquinone (CQ) and common initiators used in the field of oral restoration composite resins.
[0028] Furthermore, the photoinitiator is selected from one or more of camphorquinone (CQ), benzil, 4,4'-dimethoxybenzil, trimethylbenzoyl, diphenylphosphine oxide, benzophenone, 1,2-diketone, anthraquinone, fluorenone, xanthones, acetophenone derivatives (such as 2,2-dimethoxy-2-phenylacetophenone, α-hydroxyacetophenone, α-aminoacetophenone), benzoin ethers, benzyl ketals, phenyl glycolate, monoacyl and diacylphosphine oxides, photosensitive pigments, etc.
[0029] Furthermore, the thermal initiator is selected from azobisisobutyronitrile (AIBN) and / or dibenzoyl peroxide (BPO), and the thermal initiator is a commonly used initiator in the industry.
[0030] Furthermore, the co-initiator is selected from one or more of ethyl 4-dimethylaminobenzoate (EDAB), dimethylaminoethyl methacrylate, and diphenyliodonium hexafluorophosphate (PI), and the co-initiator is a commonly used initiator in the industry.
[0031] The fourth object of the present invention is to provide a low-shrinkage composite resin for oral restoration, which is prepared by the method for preparing the low-shrinkage composite resin for oral restoration as described above.
[0032] The novel POSS designed by the present invention has a cage-like molecular structure, an expansion functional group and a low-shrinkage oral resin monomer that can participate in the reaction. When the monomer is introduced into a resin matrix, the shrinkage rate of the oral repair composite resin can be reduced, and the generation of microcracks, microleakage and secondary caries can be reduced. The double bonds in the novel POSS monomer can react with the organic matrix to form a cross-linked network, and the epoxy group ring-opening reaction increases the volume after the reaction and reduces the shrinkage rate of the resin. The novel POSS is combined with an organic component and a filler to prepare an oral repair composite resin, which can improve the mechanical properties and stability of the oral repair resin. The low-shrinkage oral repair composite resin prepared by the present invention based on the novel POSS has excellent low shrinkage and hydrophobicity, and has little effect on mechanics and is particularly suitable for preparing high-performance low-shrinkage oral resins.
[0033] A fifth object of the present invention is to provide a use of the low-shrinkage composite resin for oral restoration as described above in the preparation of oral restoration materials.
[0034] Compared with the prior art, the present invention has the following beneficial effects: The invention uses trimethoxy[2-(7-oxabicyclo[4.1.0]hept-3-yl)ethyl]silane and double-bond-containing silane as raw materials and prepares a novel POSS having an epoxy shrinkage group and a reactive double bond through a hydrolysis-polycondensation method. The preparation method provided by the invention is simple and suitable for industrial production and application.
[0035] The novel POSS prepared by the present invention has very excellent low shrinkage and hydrophobicity, and good mechanical properties. The novel POSS monomer synthesized by the present invention simultaneously introduces double bonds and epoxy expansion groups, which can reduce the polymerization shrinkage rate of the low shrinkage composite resin for oral restoration, improve mechanical properties and reduce water penetration.
[0036] The invention provides a method for preparing a low-shrinkage composite resin for oral restoration. The preparation raw materials include organic components, prepared low-shrinkage novel POSS components, fillers and functional components required in the field of oral resins.
[0037] The oral restoration low-shrinkage composite resin prepared by the invention, which contains a novel POSS having a reactive double bond and an epoxy shrinkage group, participates in resin matrix polymerization through the double bonds in the POSS, thereby increasing mechanical interlocking force and improving the mechanical properties and stability of the oral restoration resin. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 Figure 1 is a structural characterization diagram of the novel POSS in the present invention, wherein Figure a is a Fourier transform infrared (FTIR) diagram of the novel POSS; Figure b is a nuclear magnetic resonance hydrogen spectrum ( 1 HNMR) spectra; Figure 2 The figure is a shrinkage performance diagram of the low shrinkage composite resin for oral restoration of the present invention, wherein the figure a is the shrinkage rate without filler; the figure b is the shrinkage rate with filler; Figure 3 The water absorption performance diagram of the low shrinkage composite resin for oral restoration of the present invention, wherein the diagram a is the swelling ratio without filler; the diagram b is the swelling ratio with filler; Figure 4 Graph showing the hydrophilic properties of the low shrinkage composite resin for oral restoration of the present invention, wherein graph a is the contact angle without filler; graph b is the contact angle with filler; Figure 5 This is a tensile performance diagram of the low shrinkage composite resin for oral restoration in the present invention; Figure 6 This is a compression performance diagram of the low shrinkage composite resin for oral restoration in the present invention; Figure 7 The graph is a bending performance graph of the low shrinkage composite resin for oral restoration in the present invention, wherein graph a is a bending stress-strain curve without filler; graph b is a bending stress-strain curve with filler. DETAILED DESCRIPTION
[0039] The principles and features of the present invention are described below in conjunction with examples. The examples are only used to explain the present invention and are not used to limit the scope of the present invention.
[0040] Example 1 A method for preparing a novel POSS having an epoxy shrinkage group and a reactive double bond comprises the following steps: adding 24.64 g of trimethoxy[2-(7-oxabicyclo[4.1.0]hept-3-yl)ethyl]silane and 24.84 g of methacryloxypropyltrimethoxysilane to a mixture filled with N 2 Put 250mL of acetone into a four-necked bottle and stir. After the solution is completely dissolved, raise the temperature to 55°C, slowly drop an aqueous solution of potassium hydroxide, condense and reflux for 24 hours to carry out a hydrolysis-polycondensation reaction. After the reaction is completed, wash with deionized water to make the solution pH = 7, separate the liquids, filter and collect the organic phase, wash, dry, filter, pass through a 0.45μm filter membrane, rotary evaporate, and vacuum dry at 40°C for 24 hours to obtain the product, i.e., the novel POSS.
[0041] Example 2 A method for preparing a novel POSS having an epoxy shrinkage group and a reactive double bond comprises the following steps: adding 49.28 g of trimethoxy[2-(7-oxabicyclo[4.1.0]hept-3-yl)ethyl]silane and 49.68 g of methacryloxypropyltrimethoxysilane to a mixture filled with N 2 Put 600mL of ether into a four-necked bottle and stir. After the solution is completely dissolved, raise the temperature to 60°C, slowly drop an aqueous solution of sodium hydroxide, condense and reflux for 30 hours to carry out a hydrolysis-polycondensation reaction. After the reaction is completed, wash with deionized water to make the solution pH = 7, separate the liquids, filter and collect the organic phase, wash, dry, filter, pass through a 0.45μm filter membrane, rotary evaporate, and vacuum dry at 40°C for 24 hours to obtain the product, i.e., the novel POSS.
[0042] Example 3 A preparation method of a novel POSS having an epoxy shrinkage group and a reactive double bond comprises the following steps: adding 123.2 g of trimethoxy[2-(7-oxabicyclo[4.1.0]hept-3-yl)ethyl]silane and 124.2 g of methacryloyloxypropyltrimethoxysilane into a four-necked bottle filled with argon, adding 1000 mL of dichloromethane and stirring, raising the temperature to 55°C after complete dissolution, slowly dropping 160 mL of potassium hydroxide (2 g) aqueous solution, condensing and refluxing for 24 hours, and performing a hydrolysis-polycondensation reaction; after the reaction is completed, washing with deionized water to make the solution pH=7, separating the liquids, suction filtering and collecting the organic phase, washing, drying, filtering, passing through a 0.45 μm filter membrane, rotary evaporation, and vacuum drying at 40°C for 24 hours to obtain a product, namely the novel POSS.
[0043] Example 4 A method for preparing a novel POSS having an epoxy shrinkage group and a reactive double bond comprises the following steps: adding 49.28 g of trimethoxy[2-(7-oxabicyclo[4.1.0]hept-3-yl)ethyl]silane and 49.68 g of methacryloxypropyltrimethoxysilane to a mixture filled with N 2 In a four-necked bottle, add 200 mL of acetonitrile and stir. After complete dissolution, raise the temperature to 65°C, slowly drop an aqueous solution of sodium hydroxide, and condense and reflux for 18 hours. After the reaction is completed, wash with deionized water to make the solution pH = 7, separate the liquid, filter and collect the organic phase, wash, dry, filter, pass through a 0.45 μm filter membrane, rotary evaporate, and vacuum dry at 40°C for 24 hours to obtain the product, i.e., the novel POSS.
[0044] Example 5 A method for preparing a low-shrinkage composite resin for oral restoration comprises the following steps: uniformly mixing organic components bisphenol A-dimethacrylate glycidyl ester (Bis-GMA) and triethylene glycol dimethacrylate (TEGDMA), adding the novel POSS prepared in Example 1, and then adding a photoinitiator system camphorquinone (CQ), ethyl 4-dimethylaminobenzoate (EDAB), and diphenyliodonium hexafluorophosphate (PI), wherein bisphenol A-dimethacrylate glycidyl ester (Bis-GMA), The weight percentages of triethylene glycol dimethacrylate (TEGDMA), the novel POSS, camphorquinone (CQ), ethyl 4-dimethylaminobenzoate (EDAB), and diphenyliodonium hexafluorophosphate (PI) are 46.5%: 46.5%: 5%: 1%: 0.4%: 0.6%. The mixture is evenly mixed in a three-roll grinder, kept away from light during the whole process, and then subjected to vacuum negative pressure treatment to obtain an uncured composite resin raw material, which is cured by ultraviolet light to obtain a resin matrix, i.e., the low-shrinkage composite resin for oral restoration.
[0045] Example 6 A method for preparing a low-shrinkage composite resin for oral restoration comprises the following steps: uniformly mixing organic components bisphenol A-dimethacrylate glycidyl ester (Bis-GMA) and triethylene glycol dimethacrylate (TEGDMA), adding the novel POSS prepared in Example 2, and then adding a photoinitiator system camphorquinone (CQ), ethyl 4-dimethylaminobenzoate (EDAB), and diphenyliodonium hexafluorophosphate (PI), wherein bisphenol A-dimethacrylate glycidyl ester (Bis-GMA) and triethylene glycol dimethacrylate (TEGDMA) are added. , triethylene glycol dimethacrylate (TEGDMA), the novel POSS, camphorquinone (CQ), ethyl 4-dimethylaminobenzoate (EDAB), and diphenyliodonium hexafluorophosphate (PI) in a weight percentage of 44%: 44%: 10%: 1%: 0.4%: 0.6%; the mixture is evenly mixed in a three-roll grinder, the whole process is kept away from light, and then subjected to vacuum negative pressure treatment to obtain an uncured composite resin raw material, which is cured by ultraviolet light to obtain a resin matrix, i.e., the low shrinkage composite resin for oral restoration.
[0046] Example 7 A method for preparing a low-shrinkage composite resin for oral restoration comprises the following steps: uniformly mixing organic components bisphenol A-dimethacrylate glycidyl ester (Bis-GMA) and triethylene glycol dimethacrylate (TEGDMA), adding the novel POSS prepared in Example 3, and then adding a photoinitiator system camphorquinone (CQ), ethyl 4-dimethylaminobenzoate (EDAB), and diphenyliodonium hexafluorophosphate (PI), wherein bisphenol A-dimethacrylate glycidyl ester (Bis-GMA), triethylene glycol dimethacrylate (TEGDMA) and the like are added. The weight percentages of ethylene glycol dimethacrylate (TEGDMA), the novel POSS, camphorquinone (CQ), ethyl 4-dimethylaminobenzoate (EDAB), and diphenyliodonium hexafluorophosphate (PI) are 41.5%: 41.5%: 15%: 1%: 0.4%: 0.6%. The mixture is evenly mixed in a three-roll grinder, and the whole process is kept away from light. The mixture is then subjected to vacuum negative pressure treatment to obtain an uncured composite resin raw material, which is cured by ultraviolet light to obtain a resin matrix, i.e., the low-shrinkage composite resin for oral restoration.
[0047] Example 8 A method for preparing a low-shrinkage composite resin for oral restoration comprises the following steps: mixing organic components bisphenol A-dimethacrylate glycidyl ester (Bis-GMA) and triethylene glycol dimethacrylate (TEGDMA) in a weight ratio of 1:1, adding the novel POSS prepared in Example 4, and then adding a filler of 500 nm SiO 2 、200nm SiO 2 、90nm SiO 2(weight ratio of 9:3:1), add photoinitiator system camphorquinone (CQ), ethyl 4-dimethylaminobenzoate (EDAB), diphenyliodonium hexafluorophosphate (PI) (weight ratio of 1:0.4:0.6), wherein the weight percentages of organic component, the novel POSS, filler, and photoinitiator system are 25.2%:2.8%:70%:2%; mix evenly with a three-roll grinder, keep the whole process away from light, and then treat with vacuum negative pressure to obtain an uncured composite resin raw material, which is cured by ultraviolet light to obtain a resin matrix, i.e., the low shrinkage composite resin for oral restoration.
[0048] Comparative Example 1 A preparation method of an oral repair composite resin comprises the following steps: uniformly mixing organic components bisphenol A-dimethacrylate glycidyl ester (Bis-GMA) and triethylene glycol dimethacrylate (TEGDMA), and then adding a photoinitiator system camphorquinone (CQ), ethyl 4-dimethylaminobenzoate (EDAB), and diphenyliodonium hexafluorophosphate (PI), wherein the weight percentages of bisphenol A-dimethacrylate glycidyl ester (Bis-GMA), triethylene glycol dimethacrylate (TEGDMA), camphorquinone (CQ), ethyl 4-dimethylaminobenzoate (EDAB), and diphenyliodonium hexafluorophosphate (PI) are 49%: 49%: 1%: 0.4%: 0.6%; uniformly mixing with a three-roll grinder, operating in a light-proof manner throughout the process, and then performing vacuum negative pressure treatment to obtain an uncured composite resin raw material, and curing with ultraviolet light to obtain a resin matrix, i.e. the oral repair low-shrinkage composite resin.
[0049] Comparative Example 2 A method for preparing a composite resin for oral restoration comprises the following steps: mixing organic components bisphenol A-dimethacrylate glycidyl ester (Bis-GMA) and triethylene glycol dimethacrylate (TEGDMA) evenly, and then adding a filler of 500 nm SiO 2 、200nm SiO 2 、90nm SiO 2(weight ratio is 9:3:1), add photoinitiator system camphorquinone (CQ), ethyl 4-dimethylaminobenzoate (EDAB), diphenyliodonium hexafluorophosphate (PI), wherein the weight percentages of bisphenol A-dimethacrylate glycidyl ester (Bis-GMA), triethylene glycol dimethacrylate (TEGDMA), filler, camphorquinone (CQ), ethyl 4-dimethylaminobenzoate (EDAB), diphenyliodonium hexafluorophosphate (PI) are 14%: 14%: 70%: 1%: 0.4%: 0.6%; mix evenly with a three-roll grinder, keep the whole process away from light, and then treat with vacuum negative pressure to obtain an uncured composite resin raw material, which is cured by ultraviolet light to obtain a resin matrix, i.e. the oral repair low shrinkage composite resin test: 1. The novel POSS prepared in Examples 1-4 was characterized by infrared spectroscopy. The Fourier transform infrared spectrometer recorded the wavelengths of 400-4000 cm -1 Spectral range and 2cm -1 The structure and composition of POSS were characterized by FTIR spectrum with high scanning rate and nuclear magnetic resonance spectrometer.
[0050] Infrared results such as Figure 1 As shown in a, 753cm -1 is the stretching vibration peak of -Si-C-; 1017cm -1 is the stretching vibration peak of -Si-O-Si-; 1711cm -1 is the stretching vibration peak of the ester group; 2931cm -1 and 2873cm -1 It is the stretching vibration peak of carbon and hydrogen. -1 A stretching vibration peak appears at 1096cm -1 The stretching vibration peak at is the vibration peak of the epoxy group in the raw material silane. In summary, the new POSS was successfully prepared.
[0051] The results of NMR are as follows Figure 1 As shown in b, the chemical shift at 0.64ppm is the characteristic peak of the methylene at a, f and c connected to silicon, 3.13ppm is the characteristic peak of the protons at j and k on the epoxy group, and the rest (0.83~2.15ppm) are the characteristic peaks of the other protons b, h, i, l, m on cyclohexane and the methylene at β-position g connected to silicon, 1.24ppm is CH 2 =C-CH 3 The chemical shift of hydrogen, i.e. e, is 5.57ppm -CH=CH 2 The chemical shift of hydrogen, i.e., position d.
[0052] 2. Use a capillary to draw samples of Examples 5-8 and Comparative Examples 1-2 with a diameter of >8 mm, measure the length of the liquid column, and then use an ultraviolet lamp to continuously irradiate from one end of the liquid column for 80 seconds. After 5 minutes, measure the length of the solidified liquid column and calculate the volume shrinkage rate. The results are shown in Figure 2 , where a is the shrinkage rate without filler, and b is the shrinkage rate with filler.
[0053] Shrinkage calculation formula:
[0054] Among them, L 0 —Liquid column length before solidification (mm), L 1 —Length of liquid column after solidification (mm).
[0055] The results showed that after adding the new POSS containing expansion functional groups, the shrinkage rate of the composite resin was significantly lower than that of the composite resin without POSS, and the minimum shrinkage rate could reach 0.12%.
[0056] After the inorganic filler is added to the sample of Example 8, its shrinkage rate is slightly increased from 0.2% when no filler is added to 0.3% compared with the sample of Example 6, with no obvious change, which can effectively prevent the occurrence of microleakage and secondary caries.
[0057] 3. Weigh the samples of Examples 5-8 and Comparative Examples 1-2 respectively, and the dry mass is the mass of the sample before swelling (G 1 ). Immerse it in phosphate buffered saline (PBS) and record the weight of the sample at different time periods (G 2 ), calculate the swelling ratio, and the results are shown in Figure 3 , where a is the swelling ratio without filler and b is the swelling ratio with filler.
[0058] Swelling ratio calculation formula:
[0059] Among them, G 1 —The weight of the sample before swelling (g), G 2 —The weight of the sample after swelling (g).
[0060] The swelling ratio diagram shows that the water absorption swelling ratio of the composite resin is stable at 1. With the addition of the hydrophobic new POSS group, the swelling ratio gradually decreases, preventing water from penetrating into the composite resin, thereby effectively preventing further hydrolysis of the composite resin and extending the service life of the composite resin.
[0061] After the inorganic filler is added to the sample of Example 8, its water absorption swelling ratio is not significantly affected (compared with the sample of Example 6).
[0062] 4. The contact angles of the samples of Examples 5-8 and Comparative Examples 1-2 were measured by a contact angle meter to determine the hydrophilicity of the composite resin. The results are shown in Figure 4 , where a is the contact angle without filler and b is the contact angle with filler.
[0063] As shown in the figure, with the addition of the new POSS, the contact angle of the composite resin gradually increases. Due to the hydrophobicity of the new POSS, the hydrophilicity of the prepared oral restoration composite resin decreases, effectively preventing the hydrolysis of the composite resin.
[0064] After the inorganic filler is added to the sample of Example 8, its contact angle does not change significantly compared with the sample of Example 6.
[0065] 5. Tensile performance test: The tensile properties of the samples of Examples 5-7 and Comparative Example 1 were measured, the tensile rate was set to 20 mm / min, and the stress-strain curves were recorded using a mechanical testing machine. The results are as follows: Figure 5 shown.
[0066] The average tensile strain of Comparative Example 1 (control group) was 85.65%, and the stress was 13.6 MPa; the average tensile strain of Example 5 (5% POSS group) was 74.68%, and the stress was 14.35 MPa; the average tensile strain of Example 6 (10% POSS group) was 76.38%, and the stress was 13.71 MPa; the average tensile strain of Example 7 (15% POSS group) was 82.96%, and the stress was 12.93 MPa.
[0067] In the tensile test, with the addition of POSS, the tensile stress decreased slightly and the tensile strain increased gradually. The results show that the addition of POSS did not significantly change the tensile properties of the resin.
[0068] 6. Compression performance test: The samples of Examples 5-7 and Comparative Example 1 were irradiated with a light curing lamp for 20 seconds respectively to prepare cylindrical specimens. They were placed in a 37°C constant temperature water bath for 24 hours before testing. The materials were polished with sandpaper and the diameter d (mm) of the specimens was measured with a vernier caliper. Then, the specimens were placed on a universal testing machine for compression testing. The loading speed was set to 0.5 mm / min, and the compression stress-strain curve was recorded. The results are shown in FIG. Figure 6 shown.
[0069] The average compressive strain of Comparative Example 1 (control group) was 61.94%, and the stress was 312.63 MPa; the average compressive strain of Example 5 (5% POSS group) was 60.17%, and the stress was 362.76 MPa; the average compressive strain of Example 6 (10% POSS group) was 65.81%, and the stress was 359.30 MPa; the average compressive tensile strain of Example 7 (15% POSS group) was 59.24%, and the stress was 343.83 MPa.
[0070] In the compression test, with the addition of POSS, the strain value first increases and then decreases, and the stress value slightly decreases. The stress value is significantly higher than that of Example 1 (control group) without adding POSS, indicating that the addition of POSS can enhance the compression performance of the resin.
[0071] 7. Bending performance test: The samples of Examples 5-8 and Comparative Examples 1-2 were irradiated with a light curing lamp for 20 seconds respectively to prepare rectangular specimens, which were placed in a constant temperature water bath at 37°C for 24 hours before testing. The material was polished with sandpaper, and the width and thickness of the specimen were measured with a vernier caliper. Then, the specimen was placed on a universal testing machine, and the loading head was aligned with the middle of the specimen strip. The specimen was loaded perpendicularly, and the loading conditions were set to a span of 10 mm and a loading speed of 1 mm / min. The bending stress-strain curve was recorded. The results are shown in Figure 7, where Figure a is a bending stress-strain curve without filler; Figure b is a bending stress-strain curve with filler.
[0072] In figure a, the average bending strain of comparative example 1 (control group) is 7.05%, and the stress is 83.40MPa; the average bending strain of embodiment 5 (5% POSS group) is 5.39%, and the stress is 68.78MPa; the average bending strain of embodiment 6 (10% POSS group) is 7.83%, and the stress is 80.75MPa; the average bending tensile strain of embodiment 7 (15% POSS group) is 7.56%, and the stress is 73.10MPa. In the bending performance test, with the addition of POSS, the strain first increases and then tends to stabilize, which is significantly higher than the control group without POSS, and the stress value first increases and then decreases, and the stress value gradually approaches the control group without POSS, indicating that the addition of POSS can enhance the strain capacity of the resin without affecting the compressive stress.
[0073] In Figure b, the average bending strain of Comparative Example 2 (control group) is 2.76%, and the stress is 117.17 MPa; the average bending strain of Example 8 (10% POSS group) is 2.13%, and the stress is 94.67 MPa.
[0074] After the filler is added to the sample of Example 8, the bending stress value of the resin increases by nearly 14 MPa compared with the sample of Example 6.
[0075] In summary, the present invention participates in the polymerization of the resin matrix through the double bonds and epoxy expansion groups in the novel POSS, thereby increasing the mechanical interlocking force, reducing the polymerization shrinkage rate of the low shrinkage composite resin for oral restoration, reducing water penetration, and further improving the mechanical properties and stability of the low shrinkage composite resin for oral restoration.
[0076] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a novel POSS, characterized in that: The method comprises the following steps: mixing trimethoxy[2-(7-oxabicyclo[4.1.0]hept-3-yl)ethyl]silane, double-bond-containing silane and an organic solvent, obtaining a liquid material through a hydrolysis-polycondensation reaction, and obtaining a product, namely the novel POSS, through liquid separation, suction filtration, washing, rotary evaporation and drying.
2. The preparation method of novel POSS according to claim 1, characterized in that, The usage ratio of the trimethoxy[2-(7-oxabicyclo[4.1.0]hept-3-yl)ethyl]silane, the double bond-containing silane and the organic solvent is 0.1-1 mol: 0.1-1 mol: 1-500 mL.
3. The preparation method of novel POSS according to claim 1, characterized in that, The pH value of the liquid material is 5-13, the reaction temperature of the hydrolysis-polycondensation reaction is 40-80° C., the reaction time is 18-36 hours, and the reaction atmosphere is air atmosphere or inert protective atmosphere.
4. The preparation method of novel POSS according to claim 1, characterized in that, The double bond-containing silane includes methacryloxypropyltrimethoxysilane; the organic solvent is selected from one or more of alcohols, ketones, ethers, esters, halogenated hydrocarbons, aromatic hydrocarbons, dimethyl sulfoxide, tetrahydrofuran, acetonitrile, and N,N-dimethylformamide; and the reagents used in the hydrolysis-polycondensation reaction include alkalis.
5. a novel POSS is prepared by the preparation method of the novel POSS as described in any one of claims 1 to 4.
6. A method for preparing a low shrinkage composite resin for oral restoration, characterized in that: The method comprises the following steps: preliminarily mixing raw material organic components, fillers, a photoinitiator system and the novel POSS described in claim 5, mixing them in a three-roll grinder, and then subjecting them to vacuum negative pressure treatment to obtain an uncured composite resin raw material, and subjecting them to photocuring to obtain a resin matrix, i.e., the low-shrinkage composite resin for oral restoration.
7. The method for preparing a low-shrinkage composite resin for oral restoration according to claim 6, characterized in that: The organic component accounts for 10-99% of the total weight of the raw materials, the filler accounts for 0-80% of the total weight of the raw materials, the photoinitiator system accounts for 1-5% of the total weight of the raw materials, and the new POSS accounts for 1-30% of the total weight of the raw materials.
8. The method for preparing a low-shrinkage composite resin for oral restoration according to claim 6, characterized in that: The organic component is selected from one or more of methyl methacrylate, ethylene glycol dimethacrylate, bisphenol A-dimethacrylate glycidyl ester, polyurethane acrylate methacrylate resin, triethylene glycol dimethacrylate, and methacrylate glycidyl ester; the filler is selected from one or more of silicon dioxide, glass powder, and ceramic powder, and the filler is a mixture of micron and nanometer levels; the photoinitiator system is selected from a photoinitiator, a combination of a photoinitiator and a thermal initiator, or a combination of a photoinitiator and a co-initiator.
9. A low shrinkage composite resin for oral restoration, prepared by the method for preparing a low shrinkage composite resin for oral restoration according to any one of claims 6 to 8.
10. Use of the low-shrinkage composite resin for oral restoration as claimed in claim 9 in the preparation of oral restoration materials.
Citation Information
Patent Citations
Nano-composite resin with low shrinking percentage for dental repair and preparation method thereof
CN103211712A
Ink composition for OLED packaging and application thereof
CN114015277A
Dental compositions containingdimethacrylate / polyhedral oligosilsesquioxane mixtureand method for preparing the same
KR1020050081605A
Low shrinkage multifunctional SSQ resins
US20110135749A1
Cited By
PE (Poly Ethylene) heat-shrinkable packaging film
CN122188264A
Multifunctional bioactive dental bulk filling composite resin and preparation method thereof
CN122272374A
